2012
DOI: 10.1111/j.1532-5415.2012.03931.x
|View full text |Cite
|
Sign up to set email alerts
|

Falls in Newly Admitted Nursing Home Residents: A National Study

Abstract: OBJECTIVES To examine the relationship between nursing home (NH) organizational characteristics and falls in newly admitted NH residents. DESIGN Observational cross-sectional study from January 1, 2006, to December 31, 2006. SETTING NHs in the United States in 2006. PARTICIPANTS Individuals (n = 230,730) admitted to a NH in 2006 without a prior NH stay and with a follow-up Minimum Data Set (MDS) assessment completed 30 days or more after admission. MEASUREMENTS The relationship between experiencing a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
49
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 32 publications
0
49
1
2
Order By: Relevance
“…This information is corroborated by the results of another study, which concluded that one out of five elderly people just admitted to institutions fall in the first days of stay. The authors attributed this to the fact that the institution staff was more familiar with older residents 15 and adjusted preventive measures and surveillance to them, to the detriment of new patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This information is corroborated by the results of another study, which concluded that one out of five elderly people just admitted to institutions fall in the first days of stay. The authors attributed this to the fact that the institution staff was more familiar with older residents 15 and adjusted preventive measures and surveillance to them, to the detriment of new patients.…”
Section: Discussionmentioning
confidence: 99%
“…Communication, organizational policies and teamwork are crucial to decreasing the prevalence of fall episodes. 15 A longitudinal, quasi-experimental study whose objective was to evaluate the efficacy of a curriculum of fall prevention based on TeamSTEPPS showed that combining team training with improved communication about fall risks was effective in reducing the prevalence of falls. 16 The first item of the last version of the protocol addresses team discussions of fall risks for different residents; the average for answers was Ẋ=3.980±1.052, and identifying risk factors is crucial to implementing preventive measures and preventing accidents.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence is higher than in residents who have been there longer, because the newcomer has to deal with an unknown environment (12)(13) . Also, the physical space and the presence of the institution staff make the place different from home (5) , which hampers risk identification and control (13) . Furthermore, the unknown environment decreases the elderly person's confidence in the execution of activities of daily living (14) .…”
Section: Discussionmentioning
confidence: 99%
“…Preparation for institutionalization is little discussed in the literature. However, it is known that one in five elderly people just admitted to LTC units fall within the first days of institutionalization (13) . The incidence is higher than in residents who have been there longer, because the newcomer has to deal with an unknown environment (12)(13) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation